Transition from vesicles to small nanometer scaled vesicles, arising from the manipulation of curvature in dialkyl chain cationic/nonionic surfactant mixed aggregates by the addition of straight chain alkanols. - Tucker, I; Penfold, J; Thomas, R; Bradbury, R; Grillo, I (2009)
The addition of straight chain alkanols to the dialkyl chain cationic/nonionic surfactant mixtures of dihexadecyl dimethyl ammonium bromide, DHDAB, and dodecaethylene monododecyl ether, C(12)E(12), has been used to manipulate the mean curvature of the self-assembled aggregates. This induces some significant structural changes and notably the formation of small unilamellar vesicles, nanometer scaled vesicles, L(sv). These structural changes have been measured and quantified using small angle neutron scattering, SANS. At a solution concentration of 25 mM, the DHDAB/C(12)E(12) mixtures have a structural evolution, from C(12)E(12) rich to DHDAB rich solution compositions, of small globular micelles, L(1), to micellar/vesicle coexistence, L(1)/L(v) or L(v)/L(1), to vesicle structures, L(v), bilamellar or multilamellar vesicles, blv or mlv. The impact of the addition of straight chain alkanols (in the range octanol to hexadecanol) depends upon the alkyl chain length and the amount of alcohol added. Furthermore, the effect of the addition of octanol and decanol appears to be distinctly different from that of the larger straight chain alkanols of dodecanol and hexadecanol. For the addition of octanol and decanol to C(12)E(12) rich DHDAB/C(12)E(12) mixtures, the alcohol is solubilized into the micellar core, and as the amount of alcohol added increases, significant micellar growth is ultimately observed. However, notably at intermediate DHDAB/C(12)E(12) solution compositions, in the region of L(1)/L(v) or L(v)/L(1) coexistance in the absence of alcohol, the addition of octanol or decanol promotes the formation of relatively small unilamellar vesicles, L(sv), nanometer sized vesicles, with a mean diameter in the range 70-140 A. For solutions that are rich in DHDAB, the addition of octanol or decanol results in a transition to L(v)/L(sv) coexistence and ultimately to L(v) formation. In contrast, the addition of the larger straight chain length alkanols, dodecanol or hexadecanol, to DHDAB/C(12)E(12) mixtures results in a somewhat different behavior. In this case, the addition of dodecanol or hexadecanol results in the transition from L(1) to L(1)/L(v) to L(v) occurring for solutions less rich in DHDAB than is observed in the absence of alcohol. That is, there is an enhanced tendency toward the formation of structures with a lower net curvature, either blv or mlv. Notably, for these mixtures, the small unilamellar nanometer scaled vesicle phase, L(sv), is absent.